Efforts To Improve Students’ Multiple Intelligence In Dealing With Era 4.0 On The Subject of Basic Chemistry - Rahmi, Ayu; Oktaviani, Coryna; Alvina, Sirry (Universitas Malikussaleh, 2020)
The study on efforts to improve students' multiple Intelligence in dealing with 4.0 era in basic chemistry courses was conducted with the aim of knowing whether the questions can be developing Multiple Intelligence and whether there was an increase in Multiple Intelligence on the student's of Faculty of Teachers Training and Education at Malikussaleh University. This study was carried out using Research and Development method or known as R&D which consists of four stages, namely the development of test questions, standardization and revision of test questions, as well as evaluation on the developed test result. The location of the study was at Faculty of Teachers Training and Education at the Malikussaleh University, located at Main Campus of Reuleut starting on the July to September 2019 with a population of all the students of Faculty of Teachers Training and Education at the Malikussaleh University. The samples in this study were students of the Department of Chemistry Education in semester 2, 4, and 6 with 20 students for each term and were taken by means of purposive sampling. Based on the results of the R&D stages, qualitative and quantitative data were obtained, then the data were analyzed using the comparison and percentage formulas. The results obtained was that there was an increase in the percentage of the value of N-gain by 82%. These results indicated a high increase from before to afterwards the treatment was implemented in this study.